Keabsahan Putusan Pengadilan yang Belum Inkracht sebagai Novum dalam Pengajuan Peninjauan Kembali - Halim, Yoefanca; Salim, Hardy (Universitas Negeri Surabaya, 2020)
A judicial institution is called good, not only if the process is honest, clean, and impartial. But in addition there are more criteria that must be met, namely principles that are open, corrective, and recordive. In this criterion, one side that deserves the attention of judicial management is the existence of a good legal remedial system as part of the principle of fairness and trial independence which are universally recognized principles. The broadest opportunity to submit corrections and recordings of decisions that have permanent legal force (inkracht) deemed unfair by justice seekers can be done through a Judicial Review. However, the Judicial Review is very limitative, one of them with the requirement for novum. But the regulation of conditions can be said to be a condition as a novum not strictly regulated. Seeing this raises a problem about,